Oral health in Brazil - Part II: Dental Specialty Centers (CEOs) - Pedrazzi, Vinícius; Dias, Katia Regina Hostilio Cervantes; Rode, Sigmar De Mello [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2008)
The concepts of health promotion, self-care and community participation emerged during the 1970s and, since then, their application has grown rapidly in the developed world, showing evidence of effectiveness. In spite of this, a major part of the population in the developing countries still has no access to specialized dental care such as endodontic treatment, dental care for patients with special needs, minor oral surgery, periodontal treatment and oral diagnosis. This review focuses on a program of the Brazilian Federal Government named CEOs (Dental Specialty Centers), which is an attempt to solve the dental care deficit of a population that is suffering from oral diseases and whose oral health care needs have not been addressed by the regular programs offered by the SUS (Unified National Health System). Literature published from 2000 to the present day, using electronic searches by Medline, Scielo, Google and hand-searching was considered. The descriptors used were Brazil, Oral health, Health policy, Health programs, and Dental Specialty Centers. There are currently 640 CEOs in Brazil, distributed in 545 municipal districts, carrying out dental procedures with major complexity. Based on this data, it was possible to conclude that public actions on oral health must involve both preventive and curative procedures aiming to minimize the oral health distortions still prevailing in developing countries like Brazil.
Keywords: Brazil; Oral health; Health policy; Program development; Dental Specialty Centers; Health program and project evaluation